Alternatives of ideologemes: Socialist and social city - Kukina, Irina; Fedchenko, Irina (project baikal, 2023)
The article studies the content of the criteria of the versions of the “socialist” and “social” city. Drawing on the examples of micro-districts implemented at the beginning of the XXI century, the article analyses a modern alternative to mass housing construction, which is gaining strength as a result of the implementation of national programs and changes in the Land an Urban Planning Codes. For the factual description of the state of the environment in the contemporary districts of Krasnoyarsk, the authors use graphic-analytical and urban morphological research methods. Fundamental approaches to the regulation of living environment are substantiated. The conclusion is made about the further development of the study.